Self-Monitoring in Speaking: In Defense of a Comprehension-Based Account - Ardi Roelofs (Journal of Cognition, 2020)
Speakers occasionally make speech errors, which may be detected and corrected. According to the comprehension-based account proposed by Levelt, Roelofs, and Meyer (1999) and Roelofs (2004), speakers detect errors by using their speech comprehension system for the monitoring of overt as well as inner speech. According to the production-based account of Nozari, Dell, and Schwartz (2011), speakers may use their comprehension system for external monitoring but error detection in internal monitoring is based on the amount of conflict within the speech production system, assessed by the anterior cingulate cortex (ACC). Here, I address three main arguments of Nozari et al. and Nozari and Novick (2017) against a comprehension-based account of internal monitoring, which concern cross-talk interference between inner and overt speech, a double dissociation between comprehension and self-monitoring ability in patients with aphasia, and a domain-general error-related negativity in the ACC that is allegedly independent of conscious awareness. I argue that none of the arguments are conclusive, and conclude that comprehension-based monitoring remains a viable account of self-monitoring in speaking.